Initial development and chemical components of sugarcane under water stress associated with arbuscular mycorrhizal fungi - Carmem C. M. de Sousa; Elvira M. R. Pedrosa; Mario M. Rolim; Uided M. T. Cavalcante; Inácio P. Monte Júnior; João V. Pereira Filho (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the effects of water stress levels in the soil and a mix (or: a mixed inoculum of four species: Claroideoglomus etunicatum, Gigasporas rosea, Acaulospora longula, Fuscutata heterogama) of arbuscular mycorrhizal fungi (AMF) on initial vegetative growth, fresh and dry biomass production, root colonization, phosphorus, proteins, enzymes and amino acid of the sugarcane variety RB 857515 under greenhouse conditions. The experiment was set in a randomized block design in a 2 x 2 factorial scheme with four treatments (T1 - 50% PC - pot capacity, with AMF; T2 - 100% PC with AMF; T3 - 50% PC without AMF; T4 - 100% PC without AMF) with 16 replicates. The water stress level of 50% PC decreased stem diameter and shoot and root fresh weight of sugarcane plants, as well as AMF in the soil and in plant roots. However, AMF and the water stress level of 50% PC, separately or combined, did not affect plant height, number of leaves, dry matter and contents of phosphorus, total soluble proteins, catalase, ascorbate peroxidase, polyphenoloxidase, peroxidase and proline of the sugarcane variety RB857515.